the ANALISIS PROSES BERFIKIR SPASIAL SISWA PADA MATERI GEOMETRI DITINJAU DARI GAYA BELAJAR - Hidayat, Kresna Nur; Fiantika, feny Rita (Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai-Nilai Islami); Vol 1 No 1 (2017): Prosiding SI MaNIs (Seminar Nasional Integrasi Matematika dan Nilai Islami ), 2017)
Spatial thinking is a basic skill that can be accessed by everyone to different degrees in different contexts to solve problems in a variety of contexts. To think spatially related needs three components, namely: the concept of space, methods of spatial representation, and spatial reasoning. Some areas of mathematical problem solving related to spatial thinking. One of them is geometry. There are two standards that are used to study the geometry and both relate to the spatial. In resolving the problem geometry everyone has their own way. How is exactly what is called a learning style. The purpose of this study was to determine the student's thinking process in solving the problems of spatial geometry of each learning style. This study is a qualitative research diskriptip. the students selected as the sample under consideration from teachers. Then visits the last student learning outcomes and then classified into 3 groups: high, medium and low. After the selected student groups are to be given a learning styles test. Then have one student who has a visual learning style, one student's learning style and one student's auditory kinesthetic learning style. The third sample will be given the test geometry indicator is adjusted to think spatially. Then Through in-depth interviews will be obtained on individual profiles in solving geometry problems. Along with interviews, researchers will observe the activity of students. Then the data obtained will be analyzed just not comparable between learning styles. So the instrument in this study is about, observation sheet and interview.